استخدام الذكاء الاصطناعي لتطوير مهارات اللغة العربية في تعلمها - Dedi Mulyanto; Muhammad Zaki; Arsyad Muhammad Ali Ridho; Khoirul Fata (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2024)
This article examines the integration of Artificial Intelligence (AI) into Arabic language learning to enhance proficiency among students. Mastering Arabic in modern educational settings is particularly challenging due to its complex grammar, various dialects, and unique script. Addressing these challenges, the research explores the effectiveness of AI-driven tools in facilitating Arabic language acquisition. Using qualitative research methods, the study investigates the application of AI technologies, such as natural language processing and machine learning algorithms, to create customized learning experiences for Arabic learners. By analyzing learner interactions and feedback, the study evaluates the effectiveness of AI platforms in overcoming language learning obstacles and improving linguistic skills. The findings indicate that AI-powered language learning applications provide personalized and adaptive learning environments tailored to individual styles and preferences. The analysis shows significant improvements in vocabulary acquisition, grammar comprehension, and conversational proficiency among learners using AI-integrated platforms. The impact of AI in Arabic language learning is substantial, offering a more engaging and interactive experience while overcoming traditional barriers. AI also provides continuous feedback and progress tracking, allowing learners to monitor their development and adjust their strategies. This research highlights the potential of AI technologies to revolutionize Arabic language education, offering innovative solutions to enhance proficiency and fluency. By leveraging AI-driven tools, educators and learners can more effectively navigate the complexities of Arabic, promoting broader access to linguistic expertise and cultural understanding.